Fe-based catalyst, preparation method and application thereof, and water-gas shift reaction method

By developing Fe-based catalysts, using spinel-type matrix composed of Fe, Al, M and O elements, and modifying alkali metals, the existing catalysts have been solved, and the problems of insufficient heat resistance, poor stability and poor environmental protection are achieved, and the efficiency of water vapor transformation reaction is achieved, reducing catalyst costs and chromium pollution.

CN119746867AActive Publication Date: 2025-04-04CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202311277979.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-04-04
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

The existing water vapor conversion catalysts have insufficient heat resistance, poor stability and poor environmental protection under high temperature and hydrothermal conditions, and have high catalyst costs and serious chromium pollution.

Method used

A Fe-based catalyst was developed, including a matrix and modified elements supported on the matrix. The matrix consists of Fe, Al, M and O elements. M is a non-Fe transition metal or alkaline earth metal. It is characterized by XRD with a spinel-type crystal structure, with an oxygen defect content of no less than 30%, and is modified by alkali metal to improve stability.

Benefits of technology

The high stability, hydrothermal resistance and sintering ability of the catalyst are achieved, the catalytic activity of the water-vapor transformation reaction is improved, the cost of the catalyst and chromium pollution are reduced, and it is suitable for conditions with low water-gas ratio, which improves hydrogen yield and reduces methane selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746867A_ABST
    Figure CN119746867A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, and discloses a Fe-based catalyst, a preparation method and application thereof, and a water-gas shift reaction method. The catalyst comprises a matrix and a modified element loaded on the matrix, the matrix comprises Fe, Al, M and O elements, and M is selected from at least one of non-Fe transition metals and alkaline earth metals; the matrix is characterized by XRD (X-Ray Diffraction) and has a spinel crystal structure; the modifying element is selected from at least one of alkali metals; wherein the content of oxygen vacancies in the catalyst is not less than 30%. The catalyst has high water vapor shift catalytic activity and good hydrothermal resistance and sintering resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to an Fe-based catalyst and a preparation method and application thereof, and a method for a water vapor shift reaction. Background Art

[0002] Hydrogen energy has attracted much attention as a potential substitute for traditional fossil fuels. In the past decade, the hydrogen energy economy has developed rapidly. The total calorific value of hydrogen fuel is 141.8MJ / kg, which is twice as high as the total calorific value of natural gas (54.0MJ / kg), and has good economic performance. Although hydrogen resources are abundant, such as water and biomass, most of the hydrogen today is extracted from traditional fossil fuels, such as crude oil and natural gas. At present, methane steam reforming (SRM) is the main mature industrial hydrogen production technology. In order to increase the hydrogen yield, the water gas shift reaction is required after the reforming process to react the excess CO and further increase the H2 content in the atmosphere, thereby increasing the hydrogen yield. The water gas shift reaction also has important applications in the field of new energy vehicles. The electrode material of the fuel cell is mainly composed of Pt, which is easily deactivated in the presence of carbon monoxide. Therefore, the water gas shift reactor is placed before the fuel cell to convert carbon monoxide into hydrogen and CO2 gas. It can be seen that the water gas shift reaction (WGS) plays an important industrial role in regulating and increasing the H2 concentration.

[0003] Commercial iron oxide catalysts use chromium oxide as a structural additive. In addition to being a structural additive to prevent the sintering of iron oxide crystals, Cr2O3 / CrO3 can also improve the inherent catalytic activity of Fe2O3. Under high-temperature hydrothermal conditions during the reaction, Cr2O3 will inhibit the growth of iron oxide grains and avoid a significant reduction in the specific surface area of ​​the catalyst. However, hexavalent chromium is a heavy metal that is toxic to humans, organisms or cells, and is also a serious environmental pollutant. The water solubility of hexavalent chromium causes it to leach from the catalyst through condensed steam or cold water. The hexavalent chromium (Cr 6+ ), the processing cost is very high. Therefore, it is urgent to develop a highly stable and highly active chromium-free catalyst.

[0004] CN107649142A discloses the use of Mn, Mg, and Cr as additives to improve the high-temperature stability of Fe-based catalysts, but still contains a low content of Cr; CN103272600A discloses a hydrothermally synthesized supported copper-iron catalyst, but its hydrothermal reaction time is long and the process is cumbersome; CN104014345A discloses the synthesis of Cu / CeO2 catalysts by deposition precipitation method, but the deposition consumes a lot of heat and the catalyst preparation cost is high.

[0005] The main problems faced by the water-gas shift reaction surface in the existing technology include serious methanogenic side reactions, low time-space yield, high catalyst cost, serious chromium pollution, etc. Therefore, how to develop chromium-free, highly selective, and simple preparation process catalysts under the premise of ensuring hydrothermal stability is the difficulty and direction of realizing the industrial application of green shift catalysts. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems of insufficient heat resistance, poor stability and poor environmental protection of water vapor shift catalysts in the prior art, and to provide an Fe-based catalyst and its preparation method and application, and a method for water vapor shift reaction. The catalyst has high stability, high resistance to hydrothermal and sintering, and high activity in catalyzing water vapor shift.

[0007] In order to achieve the above object, the present invention provides an Fe-based catalyst, which includes a matrix and a modifying element supported on the matrix, wherein the matrix includes Fe, Al, M and O elements, and M is selected from at least one of non-Fe transition metals and alkaline earth metals; and the matrix has a spinel crystal structure as characterized by XRD;

[0008] The modifying element is selected from at least one of alkali metals;

[0009] Wherein, the content of oxygen defects in the catalyst is not less than 30%.

[0010] A second aspect of the present invention provides a method for preparing an Fe-based catalyst, comprising the following steps:

[0011] (1) mixing a soluble compound of Fe, a soluble compound of Al, a soluble compound of M, and a solvent to obtain a mixed solution; wherein M is selected from at least one of a non-Fe transition metal and an alkaline earth metal;

[0012] (2) mixing the mixed solution with a complexing agent under stirring to obtain a gel;

[0013] (3) drying and calcining the gel to obtain a matrix;

[0014] Wherein, the calcination temperature does not exceed 400°C;

[0015] (4) A modifying element is supported on the matrix, wherein the modifying element is at least one selected from alkali metals.

[0016] The third aspect of the present invention provides the use of the Fe-based catalyst described in the first aspect or the Fe-based catalyst prepared by the preparation method described in the second aspect in a water gas shift reaction.

[0017] A fourth aspect of the present invention provides a method for a water gas shift reaction, comprising: contacting a raw gas containing CO, water vapor and a catalyst under water gas shift reaction conditions to perform a water gas shift reaction;

[0018] Wherein, the catalyst is the Fe-based catalyst described in the first aspect or the Fe-based catalyst prepared by the preparation method described in the second aspect.

[0019] The oxygen defect content in the Fe-based catalyst provided by the present invention is not less than 30%. By controlling the high oxygen defect in the Fe-based spinel catalyst, it is beneficial to improve the catalytic activity and heat-resistant activity of the catalyst in the water vapor shift reaction. Further, the surface modification is performed by alkali metal, which can have high stability, high hydrothermal resistance and anti-sintering ability, and high activity in catalyzing water vapor shift. The preparation method provided by the present invention forms a uniformly dispersed precursor by complexing, and forms a spinel-type catalyst with certain oxygen defects by controlling the roasting temperature and doping metal. In a preferred case, the catalyst has a fluffy, porous, uneven spinel surface, has a high specific surface area, and can further improve the catalytic activity. The Fe-based catalyst of the present invention is low in cost, and the production process is free of toxic substances. It is suitable for conditions with low water-gas ratios, can improve the hydrogen yield of water vapor shift, and reduce methane selectivity. At the same time, the catalyst has good heat-resistant activity, and the specific surface and activity are kept good after high-temperature treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is the XRD pattern of the matrix prepared in Example 1;

[0021] Figure 2 is the XPS O1s curve of the catalysts prepared in Example 1 and Example 3;

[0022] Figure 3 This is the stability curve of the catalyst prepared in Example 1 after 100 hours of reaction. DETAILED DESCRIPTION

[0023] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0024] The first aspect of the present invention provides an Fe-based catalyst, the catalyst comprising a matrix and a modifying element supported on the matrix, the matrix comprising Fe, Al, M and O elements, M being selected from at least one of non-Fe transition metals and alkaline earth metals; the matrix having a spinel crystal structure as characterized by XRD;

[0025] The modifying element is selected from at least one of alkali metals;

[0026] Wherein, the content of oxygen defects in the catalyst is not less than 30%.

[0027] The inventors of the present invention have found in their research that controlling the Fe-based spinel catalyst to have a high oxygen defect is beneficial to improving the catalytic activity and heat resistance of the catalyst in the water gas shift reaction. In the present invention, "oxygen defect" refers to a vacancy formed in a metal oxide crystal when an oxygen atom leaves the lattice position.

[0028] In the present invention, the oxygen defect content in the catalyst is characterized by XPS. XPS characterization is carried out on an ESCALAB 250 X-ray photoelectron spectrometer produced by Thermo Fisher-VG, the excitation source is AlKαX-ray with a monochromatic power of 150W, the reduction conditions are a heating rate of 5°C / min, the gas is pure H2, the reaction pressure is 0.12MPa, and the reduction is 3h after heating to the target temperature. The obtained XPS O1s curve is peaked, and the peak at the position of 531±0.5eV is the characteristic peak of oxygen defects. The ratio of the peak area of ​​the characteristic peak of oxygen defects to the total area of ​​the O1s peak is calculated and recorded as the oxygen defect content.

[0029] In some preferred embodiments of the present invention, the oxygen defect content in the catalyst is 30-60%, for example, it can be 30%, 35%, 40%, 45%, 50%, 55%, 60% and other typical but non-limiting content values ​​or ranges therebetween. Preferably, the oxygen defect content in the catalyst is 40-50%. In the above preferred case, it is beneficial to further improve the catalytic activity and heat resistance activity of the catalyst in the water gas shift reaction.

[0030] According to the present invention, "characterized by XRD, the matrix has a spinel crystal structure" means that through X-ray diffraction testing, the XRD characteristic peaks of the matrix conform to the spinel structure characteristics and there are no obvious impurity peaks, indicating that the matrix has a spinel crystal structure.

[0031] It is to be understood that, in the present invention, it is not excluded that the matrix also contains Fe, Al or M elements in the form of a single oxide, as long as the matrix has the above XRD characteristics.

[0032] In the present invention, the conditions of the X-ray diffraction test include: using a Bruker D5005 diffractometer to perform XRD analysis on a fresh catalyst sample, using Cu Kα rays (0.154184 nm), a scanning range of 3°-80°, and a scanning rate of 0.02° / s. Using a set of EVA software based on the JCPDS method to analyze and identify the phases in the sample.

[0033] According to some preferred embodiments of the present invention, in the matrix, the molar ratio of Fe element to Al element is 1:(0.01-0.2), preferably 1:(0.05-0.15). Under the above preferred element ratio, it is beneficial to improve the structural stability of the catalyst under hydrothermal state.

[0034] Preferably, in the matrix, the content of Fe calculated as ferric oxide is 40-98.5wt%, preferably 60-90wt%, the content of Al calculated as aluminum oxide is 0.5-20wt%, preferably 1-10wt%, and the content of M calculated as oxide is 1-40wt%, preferably 1-35wt%, wherein the oxide of M is the divalent oxide of M metal.

[0035] In the present invention, the content of components in the matrix is ​​obtained by XRF testing.

[0036] In a preferred embodiment, the catalyst provided by the present invention has a fluffy, porous, non-uniform spinel surface, thereby having a higher specific surface area. Preferably, the specific surface area of ​​the catalyst is 50-120 m 2 / g, preferably 60-100m 2 / g. Within the above preferred specific surface area range, it is beneficial to improve the water vapor conversion activity.

[0037] In the present invention, the specific surface area of ​​the catalyst is analyzed by using low-temperature N2 constant temperature adsorption-desorption and conventional BET calculation processing. Before analysis, the sample is dried at 120°C for 2h and then evacuated under vacuum at 300°C. The adsorption medium is high-purity nitrogen. The adsorption / desorption experiment is carried out under liquid nitrogen cooling conditions (-196°C).

[0038] In the present invention, the selection range for M is relatively wide, and non-Fe transition metals and alkaline earth metals can be applied to the present invention. For example, it can be at least one of Co, Ni, Cu, Cr, Mn, Zr, Ti, La, Mo, W, Ru, Rh, Pd, Zn, Ma, Ca, Sr and Ba, preferably at least one of Co, Ni, Cu, Cr, Mn, Mg, Ca, Sr and Ba. In order to improve the catalyst stability, hydrothermal resistance and sintering resistance, while also having environmental protection, more preferably, the M is selected from at least one of Co, Ni and Cu. The above-mentioned preferred M metal composition is used to form an Fe-based spinel structure rich in oxygen defects with Fe and Al, and is also conducive to further improving the water vapor shift activity and heat resistance of the catalyst.

[0039] In the present invention, the modifying element is selected from at least one of alkali metals, preferably, the modifying element is selected from at least one of Li, Na, K, Rb, and Cs, more preferably K and / or Cs. In the above preferred case, it is beneficial to improve the water vapor shift activity.

[0040] The present invention has a wide range of selection for the content of each component in the catalyst. Preferably, based on the total amount of the catalyst, the content of the matrix is ​​90-99.9wt%, and the content of the modifying element calculated as oxide is 0.1-10wt%. Further preferably, based on the total amount of the catalyst, the content of the matrix is ​​95-99.8wt%, and the content of the modifying element calculated as oxide is 0.2-5wt%.

[0041] In the present invention, the content of each component in the catalyst is obtained by X-ray fluorescence (XRF) testing.

[0042] A second aspect of the present invention provides a method for preparing an Fe-based catalyst, comprising the following steps:

[0043] (1) mixing a soluble compound of Fe, a soluble compound of Al, a soluble compound of M, and a solvent to obtain a mixed solution; wherein M is selected from at least one of a non-Fe transition metal and an alkaline earth metal;

[0044] (2) mixing the mixed solution with a complexing agent under stirring to obtain a gel;

[0045] (3) drying and calcining the gel to obtain a matrix;

[0046] Wherein, the calcination temperature does not exceed 400°C;

[0047] (4) A modifying element is supported on the matrix, wherein the modifying element is at least one selected from alkali metals.

[0048] The preparation method provided by the present invention forms a uniformly dispersed precursor by complexation, forms a spinel catalyst with certain oxygen defects by controlling the calcination temperature and doping metals, and further loads alkali metals, which is beneficial to the dispersion of the alkali metals. The alkali metals and Fe-based spinel oxides act synergistically, and the prepared catalyst has high stability, high hydrothermal and sintering resistance, and high activity in catalyzing water vapor conversion.

[0049] According to the present invention, through X-ray diffraction testing, the XRD characteristic peaks of the matrix conform to the characteristics of the spinel structure, and there are no obvious impurity peaks, indicating that the matrix has a spinel crystal structure.

[0050] The present invention has a wide range of selection for the amount of soluble compounds of Fe, soluble compounds of Al, and soluble compounds of M, as long as the obtained Fe-based spinel oxide has the above-mentioned chemical composition, and those skilled in the art can make the selection according to actual conditions.

[0051] Preferably, calculated on the basis of metal elements, the molar ratio of the soluble compound of Fe to the soluble compound of Al is 1-25:1, preferably 5-15:1.

[0052] According to some preferred embodiments of the present invention, calculated as metal elements, the ratio of the total molar amount of the soluble compounds of Fe and Al to the molar amount of the soluble compounds of M is 1-20:1, preferably 1-10:1.

[0053] The present invention has no particular limitation on the type and amount of the solvent in step (1), as long as the soluble compounds of Fe, Al and M can be fully dissolved and mixed. Those skilled in the art can select the solvent according to actual conditions. For example, the solvent can be water.

[0054] According to some preferred embodiments of the present invention, in the mixed solution, the total molar concentration of Fe, Al and M, calculated as metal elements, is 0.01-5 mol / L, preferably 0.1-1 mol / L.

[0055] The present invention has no particular requirements for the specific selection of the soluble compounds of Fe, Al and M. Conventional soluble inorganic salts or organic salts containing the above metal elements can be used as long as they can provide Fe, Al and M elements.

[0056] According to the present invention, the M element has the same definition as that of M in the catalyst described in the first aspect, and will not be described in detail herein.

[0057] According to some preferred embodiments of the present invention, the soluble compound of Fe, the soluble compound of Al and the soluble compound of M are each independently selected from at least one of metal nitrates, sulfates, halides, acetates and formates, preferably metal nitrates.

[0058] The soluble compounds of Fe, Al and M may also contain crystal water, which is well known to those skilled in the art.

[0059] According to some preferred embodiments of the present invention, the complexing agent is selected from at least one of citric acid, oxalic acid, monoethanolamine, diethanolamine, triethanolamine and ethylenediaminetetraacetic acid, preferably citric acid. The above preferred embodiments are beneficial to further promote the dispersion of the catalyst.

[0060] According to some preferred embodiments of the present invention, the ratio of the amount of the complexing agent to the total molar amount of the soluble compounds of Fe, Al and M in terms of metal elements is 0.1-1:1, preferably 0.2-0.8:1. Within the above preferred dosage range, a stable spinel structure is formed.

[0061] In the present invention, the complexing agent may be provided in the form of an aqueous solution of the complexing agent. Preferably, the concentration of the aqueous solution of the complexing agent is 0.01-2 mol / L, preferably 0.1-1 mol / L.

[0062] The present invention has no particular limitation on the mixing conditions in step (2), as long as it is conducive to forming a uniform gel. Preferably, the mixing temperature in step (2) is 40-90° C., preferably 50-80° C. The present invention has no particular requirements on the stirring conditions, and stirring conditions in the art can be used.

[0063] In the present invention, the solvent in the gel is removed by drying in step (3). Preferably, the drying conditions include: a temperature of 90-150° C., preferably 90-120° C.; and a time of 0.5-20 h, preferably 8-15 h.

[0064] In the present invention, in order to form a good spinel structure with an appropriate amount of oxygen defects, the calcination temperature in step (3) does not exceed 400° C. In the prior art, the calcination temperature of spinel oxide prepared by the sol-gel method is usually above 600° C.

[0065] In a further preferred case, in step (3), the calcination temperature does not exceed 350° C., preferably 200-350° C. The above preferred embodiment is conducive to further forming a stable spinel structure.

[0066] Preferably, the calcination time is 0.5-12 h, preferably 1-5 h.

[0067] The present invention has no particular limitation on the specific loading method in step (4), and any conventional loading method and conditions in the art may be used. For example, an impregnation method of a soluble compound solution containing a modifying element may be used, or a physical mixing method such as mechanical grinding of an alkali metal salt, oxide or hydroxide with a matrix may be used.

[0068] In the present invention, the selection range of the modifying element is the same as that defined in the first aspect and will not be repeated here.

[0069] According to some preferred embodiments of the present invention, in step (4), the loading comprises: impregnating the substrate with a solution of a soluble compound containing a modifying element, and then performing a second drying and a second calcination.

[0070] The present invention has no particular limitation on the specific method of the impregnation, which may be equal volume impregnation or excess impregnation. Preferably, the impregnation is equal volume impregnation.

[0071] Preferably, the amount of the solution of the soluble compound containing the modifying element and the matrix is ​​such that, based on the total amount of the prepared catalyst, the content of the matrix is ​​90-99.9wt%, preferably 95-99.8wt%; the content of the modifying element calculated as oxide is 0.1-10wt%, preferably 0.2-5wt%.

[0072] Preferably, the concentration of the modifying element in the solution of the soluble compound containing the modifying element is 0.1-0.5 mol / L.

[0073] The solvent in the solution may be water.

[0074] Preferably, the soluble compound of the modifying element is selected from alkali metal salts and / or hydroxides. Preferably, the alkali metal salts may be metal inorganic salts and / or organic salts. The inorganic salts may be nitrates, sulfates, halides, etc. The organic salts may be formates, acetates, etc. Preferably, the soluble compound of the modifying element is an alkali metal nitrate or an alkali metal hydroxide.

[0075] Preferably, the second drying is carried out at a temperature of 90-150° C. and for a time of 0.5-12 h.

[0076] Preferably, the second calcination is performed at a temperature of 200-500° C. and for a time of 0.5-12 h.

[0077] The third aspect of the present invention provides the use of the above-mentioned Fe-based catalyst or the Fe-based catalyst prepared by the preparation method described in the second aspect in a water gas shift reaction.

[0078] A fourth aspect of the present invention provides a method for water gas shift reaction, the method comprising: contacting a raw gas containing CO, water vapor and a catalyst to perform water gas shift reaction under water gas shift reaction conditions;

[0079] Wherein, the catalyst is the Fe-based catalyst described in the first aspect or the Fe-based catalyst prepared by the preparation method described in the second aspect.

[0080] Preferably, the water gas shift reaction conditions include: reaction temperature of 300-500°C, preferably 320-380°C; reaction pressure of 0.1-5MPa, preferably 1-3MPa; mass space velocity of feed gas of 2000-20000h -1 , preferably 5000-15000h -1 ; The water-to-carbon ratio is 2.4-6, preferably 3-4.

[0081] Preferably, the method further comprises: before the contacting, subjecting the catalyst to a reduction pretreatment in a reducing atmosphere containing H2 and / or CO.

[0082] Preferably, the reduction pretreatment conditions include: temperature of 200-600°C; time of 1-12h; pressure of 0.1-1MPa, and air velocity of 500-20000h -1 .

[0083] Preferably, the reducing atmosphere may further contain a non-reducing gas, which is water vapor and / or carbon dioxide. Preferably, in the reducing atmosphere, the ratio of the total volume of H2 and / or CO to the volume of the non-reducing gas is 1-2:1, preferably 1.2-1.6:1.

[0084] In a further preferred case, the reducing atmosphere can be provided directly by the raw gas.

[0085] The present invention will be described in detail below through examples.

[0086] In the following examples and comparative examples, unless otherwise specified, the raw materials used were commercially available.

[0087] The specific surface area of ​​the catalyst was analyzed by low-temperature N2 constant temperature adsorption-desorption and conventional BET calculation. Before analysis, the sample was dried at 120℃ for 2h and then evacuated under vacuum at 300℃. The adsorption medium was high-purity nitrogen. The adsorption / desorption experiment was carried out under liquid nitrogen cooling conditions (-196℃).

[0088] The content of each component in the catalyst was tested by X-ray fluorescence analysis (XRF).

[0089] The oxygen defect content in the catalyst was measured by X-ray photoelectron spectroscopy (XPS) method.

[0090] Example 1

[0091] (1) 4.83 g of Cu(NO3)2·3H2O, 16.16 g of Fe(NO3)3·9H2O and 1.87 g of Al(NO3)3·9H2O were dissolved in 80 mL of deionized water and stirred to obtain a mixed solution.

[0092] (2) Dissolve 5.8 g of citric acid in 100 mL of deionized water and stir to dissolve. Mix the two solutions in a water bath at 80° C. and stir to obtain a gel.

[0093] (3) The obtained gel was dried in an oven at 100°C for 12 hours, and then calcined at 200°C for 2 hours, and then ground to obtain a matrix. The obtained matrix powder was subjected to X-ray diffraction analysis. Figure 1 As shown, it can be seen that the XRD curve of the matrix has a characteristic peak of the spinel structure, and there are no other impurity peaks, indicating that the matrix has a spinel crystal structure. Through XRF testing and calculation, the molar ratio of Fe element to Al element in the matrix is ​​1:0.12. Based on the total amount of the matrix, the content of Fe2O3 is 63.4wt%, the content of Al2O3 is 5wt%, and the content of CuO is 31.5wt%.

[0094] (4) Pour 3 mL of 0.56 mol / L KOH aqueous solution into the above powder and grind it evenly. The obtained wet powder is dried in an oven at 100°C for 12 hours and then calcined at 340°C for 3 hours. The prepared sample is ground into powder and sieved with a 40-60 mesh sieve. The obtained catalyst is recorded as A1. The composition of the catalyst is shown in Table 1. The O1s curve of the catalyst tested by the XPS method is shown in Figure 2 The calculated oxygen defect content is shown in Table 1.

[0095] Example 2

[0096] (1) Dissolve 1.52 g of Ni(NO3)2·6H2O, 20.2 g of Fe(NO3)3·9H2O and 1.87 g of Al(NO3)3·9H2O in 100 mL of deionized water and stir to obtain a mixed solution.

[0097] (2) Dissolve 7.0 g of citric acid in 100 mL of deionized water and stir to dissolve. Mix the two solutions in a water bath at 80° C. and stir to obtain a gel.

[0098] (3) The obtained gel was dried in an oven at 100°C for 12 hours, and then calcined at 200°C for 2 hours. The matrix was obtained after grinding. The obtained matrix powder was subjected to X-ray diffraction analysis. Figure 1 Similarly, XRD testing shows that the matrix has a spinel crystal structure. XRF testing and calculation show that the molar ratio of Fe element to Al element in the matrix is ​​1:0.1. Based on the total amount of the matrix, the content of Fe2O3 is 86.1wt%, the content of Al2O3 is 5.5wt%, and the content of NiO is 8.4wt%.

[0099] (4) Pour 2.5 mL of 0.135 mol / L Cs2CO3 aqueous solution into the above powder and grind it evenly. The obtained wet powder is dried in an oven at 100°C for 12 hours and then calcined at 340°C for 3 hours. The prepared sample is ground into powder and sieved with a 40-60 mesh sieve. The obtained catalyst is recorded as A2. The composition of the catalyst is shown in Table 1. The oxygen defect content tested and calculated by the XPS method is shown in Table 1.

[0100] Example 3

[0101] (1) 8.73 g of Co(NO3)2·6H2O, 24.2 g of Fe(NO3)3·9H2O and 2.81 g of Al(NO3)3·9H2O were dissolved in 120 mL of deionized water and stirred to obtain a mixed solution.

[0102] (2) Then, 8.65 g of citric acid was dissolved in 100 mL of deionized water and stirred to dissolve. The two solutions were mixed and stirred in a water bath at 80° C. to obtain a gel.

[0103] (3) The obtained gel was dried in an oven at 100°C for 12 hours, and then calcined at 200°C for 2 hours. The matrix was obtained after grinding. The obtained matrix powder was subjected to X-ray diffraction analysis. Figure 1 Similarly, XRD testing shows that the powder has a spinel crystal structure. XRF testing and calculation show that the molar ratio of Fe element to Al element in the matrix is ​​1:0.12. Based on the total amount of the matrix, the content of Fe2O3 is 64.6wt%, the content of Al2O3 is 5.1wt%, and the content of CoO is 30.3wt%.

[0104] (4) Pour 3.8 mL of 0.85 mol / L KNO3 aqueous solution into the above powder and grind it evenly. The obtained wet powder is dried in an oven at 110°C for 12 hours and then roasted at 340°C for 3 hours. The prepared sample is ground into powder and sieved with a 40-60 mesh sieve. The obtained catalyst is recorded as A3. The composition of the catalyst is shown in Table 1. The O1s curve of the catalyst tested by the XPS method is shown in Figure 2 The calculated oxygen defect content is shown in Table 1.

[0105] Example 4

[0106] The method of Example 1 is used, except that the mass of Cu(NO3)2·3H2O is 4.83g, the mass of Fe(NO3)3·9H2O is 16.16g, and the mass of Al(NO3)3·9H2O is 1.01g. The calcination temperature used in step (3) is 400°C. XRD test shows that the powder has a spinel crystal structure. XRF test and calculation show that the molar ratio of Fe element to Al element in the matrix is ​​1:0.067. Based on the total amount of the matrix, the content of Fe2O3 is 64.9wt%, the content of Al2O3 is 2.8wt%, and the content of CuO is 32.3wt%.

[0107] K was loaded in the same manner as in Example 1, and the obtained catalyst was denoted as A4. The composition of the catalyst is shown in Table 1.

[0108] Example 5

[0109] The method of Example 1 is followed, except that the concentration of the KOH aqueous solution is 1.8 mol / L.

[0110] The prepared catalyst is denoted as A5, and the composition of the catalyst is shown in Table 1.

[0111] Comparative Example 1

[0112] Dissolve 4.83g of Cu(NO3)2·3H2O, 16.16g of Fe(NO3)3·9H2O and 1.01g of Al(NO3)3·9H2O in 160mL of deionized water and stir to obtain a mixed solution. Then pour 2mol / L Na2CO3 solution into the above solution, stir during neutralization, titrate to pH 8, heat-boil and age at 80℃ for 1h, filter and wash, dry the obtained precipitate in an oven at 100℃ for 12h, and then roast at 200℃ for 2h, grind to obtain powder. The obtained powder was subjected to X-ray diffraction analysis, and Figure 1Similarly, XRD testing shows that the powder has a spinel crystal structure. XRF testing and calculation show that the molar ratio of Fe element to Al element in the matrix is ​​1:0.067. Based on the total amount of the matrix, the content of Fe2O3 is 64.9wt%, the content of Al2O3 is 2.8wt%, and the content of CuO is 32.2wt%.

[0113] 3 mL of 0.56 mol / L KOH aqueous solution was poured into the above powder and ground evenly. The obtained wet powder was dried in an oven at 100°C for 12 hours and then calcined at 400°C for 3 hours. The prepared sample was ground into powder and sieved with a 40-60 mesh screen. The obtained catalyst was recorded as DA1. The composition of the catalyst is shown in Table 1.

[0114] Comparative Example 2

[0115] The method of Example 1 is followed, except that step (4) is not performed, and the substrate prepared in step (3) of Example 1 is used as a catalyst, denoted as DA2. The composition of the catalyst is shown in Table 1.

[0116] Comparative Example 3

[0117] The method of Example 1 is followed, except that the calcination temperature in step (3) is 600°C.

[0118] The prepared catalyst is recorded as DA3, and the composition of the catalyst is shown in Table 1.

[0119] Table 1

[0120]

[0121] Test Case

[0122] (1) Catalyst activity evaluation:

[0123] 0.5 g of the catalysts of the above embodiments and comparative examples were respectively loaded into a reaction tube with an inner diameter of 8 mm and pretreated at 400° C. for 2 h. The pretreatment was carried out under normal pressure and dry gas atmosphere. The composition (volume content) under the dry gas atmosphere was as follows: CO / CO2 / H2 / N2=24.7% / 8.3% / 49.5% / 17.5%, and the dry gas space velocity was 20000 h -1 , water-to-carbon ratio 1.2.

[0124] Then adjust the dry gas airspeed to 12000h -1 , water-carbon ratio 3.0, reacted at normal pressure and 300°C for 2h, and the product composition was analyzed by gas chromatography. The evaluation results are shown in Table 2. The stability curve of the catalyst prepared in Example 1 for 100h reaction is shown in Figure 3 shown.

[0125] in,

[0126]

[0127]

[0128] In the above formula, F CO(进) Refers to the CO flow rate at the reactor inlet, F CO(出) refers to the CO flow rate at the reactor outlet (mL / min), F CH4(进) refers to the CH4 flow rate at the reactor inlet (mL / min), F CH4(出) refers to the CH4 flow rate at the reactor outlet (mL / min), F H2(进) refers to the H2 flow rate at the reactor inlet (mL / min), F H2(出) refers to the H2 flow rate at the reactor outlet (mL / min), V m is the molar volume of the gas (L / mol), M cat is the mass of the loaded catalyst (g).

[0129] (2) Heat resistance activity test

[0130] The atmosphere and space velocity were the same as those of the above-mentioned water vapor shift reaction, except that the temperature was first maintained at 530°C for 8 h, then cooled to 300°C for 4 h, and the CO conversion rate was tested as the thermostable activity;

[0131] Then the activity retention rate after heat resistance was calculated by the following formula, and the results are shown in Table 2.

[0132] The initial activity is the CO conversion rate measured under the conditions of test example (1).

[0133] Table 2

[0134]

[0135] Combining the results of Table 1 and Table 2, it can be seen that by comparing the embodiment with comparative examples 1 and 3, it can be seen that the catalyst prepared by the present invention has a high oxygen defect, and by controlling the high oxygen defect in the Fe-based spinel catalyst, it is beneficial to improve the catalytic activity and heat resistance activity of the catalyst in the water gas shift reaction. By comparing Example 1 and Comparative Example 2, it can be seen that surface modification of the matrix by alkali metal can improve the stability of the catalyst and the activity of catalytic water gas shift.

[0136] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An Fe-based catalyst, characterized in that the catalyst comprises a matrix and a modifying element supported on the matrix, the matrix comprises Fe, Al, M and O elements, M is selected from at least one of a non-Fe transition metal and an alkaline earth metal; and the matrix has a spinel crystal structure as characterized by XRD; The modifying element is selected from at least one of alkali metals; Wherein, the content of oxygen defects in the catalyst is not less than 30%.

2. The catalyst according to claim 1, wherein the oxygen defect content in the catalyst is 30-60%, preferably 40-50%; Preferably, the specific surface area of ​​the catalyst is 50-120 m 2 / g, preferably 60-100m 2 / g.

3. The catalyst according to claim 1 or 2, wherein M is selected from at least one of Co, Ni, Cu, Cr, Mn, Zn, Mg, Ca, Sr and Ba, preferably at least one of Co, Ni and Cu; Preferably, the modifying element is selected from at least one of Li, Na, K, Rb and Cs, preferably K and / or Cs.

4. The catalyst according to any one of claims 1 to 3, wherein the content of the matrix is ​​90-99.9wt%, preferably 95-99.8wt%, based on the total amount of the catalyst; the content of the modifying element in terms of oxide is 0.1-10wt%, preferably 0.2-5wt%; Preferably, in the matrix, the molar ratio of Fe element to Al element is 1:(0.01-0.2), preferably 1:(0.05-0.15); Preferably, in the matrix, the content of Fe calculated as ferric oxide is 40-98.5wt%, the content of Al calculated as aluminum oxide is 0.5-20wt%, and the content of M calculated as oxide is 1-40wt%.

5. A method for preparing an Fe-based catalyst, characterized in that it comprises the following steps: (1) mixing a soluble compound of Fe, a soluble compound of Al, a soluble compound of M, and a solvent to obtain a mixed solution; wherein M is selected from at least one of a non-Fe transition metal and an alkaline earth metal; (2) mixing the mixed solution with a complexing agent under stirring to obtain a gel; (3) drying and calcining the gel to obtain a matrix; Wherein, the calcination temperature does not exceed 400°C; (4) A modifying element is supported on the matrix, wherein the modifying element is at least one selected from alkali metals.

6. The preparation method according to claim 5, wherein M is selected from at least one of Co, Ni, Cu, Cr, Mn, Zn, Ma, Ca, Sr and Ba, preferably at least one of Co, Ni and Cu; Preferably, the molar ratio of the soluble compound of Fe to the soluble compound of Al is 1-25:1, preferably 5-15:1, calculated as metal elements; Preferably, in terms of metal elements, the ratio of the total molar amount of the soluble compound of Fe and the soluble compound of Al to the molar amount of the soluble compound of M is 1-20:1, preferably 1-10:1; Preferably, in the mixed solution, the total molar concentration of Fe, Al and M, calculated as metal elements, is 0.01-5 mol / L, preferably 0.1-1 mol / L; Preferably, the soluble compound of Fe, the soluble compound of Al and the soluble compound of M are each independently selected from inorganic salts and / or organic salts of metals, preferably at least one of nitrates, sulfates, halides, acetates and formates.

7. The preparation method according to claim 5 or 6, wherein the complexing agent is selected from at least one of citric acid, oxalic acid, monoethanolamine, diethanolamine, triethanolamine and ethylenediaminetetraacetic acid; Preferably, the ratio of the amount of the complexing agent to the total molar amount of the soluble compound of Fe, the soluble compound of Al and the soluble compound of M calculated as metal elements is 0.1-1:1; Preferably, the mixing temperature in step (2) is 40-90°C.

8. The preparation method according to any one of claims 5 to 7, wherein in step (3), the drying conditions include: a temperature of 90-150°C and a time of 0.5-20h; Preferably, the calcination temperature does not exceed 350°C, preferably 200-350°C; Preferably, the calcination time is 0.5-12h.

9. The preparation method according to any one of claims 5 to 8, wherein the modifying element is selected from at least one of Li, Na, K, Rb, and Cs, preferably K and / or Cs; Preferably, in step (4), the loading comprises: impregnating the substrate with a solution of a soluble compound containing a modifying element, followed by a second drying and a second calcination; Preferably, the impregnation is equal volume impregnation or excess impregnation; Preferably, the concentration of the solution containing the soluble compound of the modifying element is 0.01-2 mol / L, calculated as the modifying element; Preferably, the amount of the solution of the soluble compound containing the modifying element and the matrix is ​​such that, based on the total amount of the prepared catalyst, the content of the matrix is ​​90-99.9wt%, preferably 95-99.8wt%; the content of the modifying element calculated as oxide is 0.1-10wt%, preferably 0.2-5wt%.

10. Use of the Fe-based catalyst according to any one of claims 1 to 4 or the Fe-based catalyst prepared by the preparation method according to any one of claims 5 to 9 in a water gas shift reaction.

11. A method for water gas shift reaction, characterized in that it comprises: under water gas shift reaction conditions, a raw gas containing CO, water vapor and a catalyst are contacted to perform water gas shift reaction; Wherein, the catalyst is the Fe-based catalyst described in any one of claims 1 to 4 or the Fe-based catalyst prepared by the preparation method described in any one of claims 5 to 9; Preferably, the water gas shift reaction conditions include: reaction temperature of 300-500°C, preferably 320-380°C; reaction pressure of 0.1-5MPa, preferably 1-3MPa; mass space velocity of feed gas of 2000-20000h -1 , preferably 5000-15000h -1 ; The water-to-carbon ratio is 2.4-6, preferably 3-4.

12. The method according to claim 11, wherein the method further comprises: before the contacting, subjecting the catalyst to a reduction pretreatment in a reducing atmosphere containing H2 and / or CO; Preferably, the reduction pretreatment conditions include: temperature of 200-600°C; time of 1-12h; pressure of 0.1-1MPa, and air velocity of 500-20000h -1 ; Preferably, the reducing atmosphere further comprises a non-reducing gas, and the non-reducing gas is water vapor and / or carbon dioxide; Preferably, in the reducing atmosphere, the ratio of the total volume of H2 and / or CO to the volume of the non-reducing gas is 1-2:1, preferably 1.2-1.6:1.

Citation Information

Patent Citations

  • Supported copper-iron water coal gas shift catalyst and preparation method thereof

    CN103272600A

  • CuO-CeO2 catalyst for water gas conversion reaction and preparation method thereof

    CN104014345A

  • Low-density iron chromium series CO transformation catalyst

    CN107649142A

  • Chromium-free water gas shift catalyst

    CN101618318A

  • Catalyst for catalytic coal gasification and preparation method of catalyst

    CN104941624A